AB0963 Inteference of ANAs in ANCa Analysis and Comparison To Clinical Outcome of Vasculitis. (15th July 2016) - Benavides Solarte, M.F.; Romero, S.M.C.; Castro, A.; Angarita, I.; Ospina, A.I.; Parra, V.; Galindo, I.; Chila, L.; Rey, L.; Villa, A.; Pineda, S.; Casas, M.; et al.
Abstract : Background: Anti-neutrophil cytoplasmic antibodies (ANCAs) are directed against the primary granules of neutrophils and monocytes and are essential in the diagnosis of vasculitis pauciimmune. The positivity of anti nuclear antibodies (ANAs) interferes with the interpretation of ANCAs leading to false positives. Objectives: Evaluate the interference of ANAs in the interpretation of ANCAs in a population with manifestations of autoimmune disease Methods: 3330 patient data involving ANCA requests between 2013 and 2015 were analyzed. Indirect immunofluorescence (IIF) was used to determine whether the samples had interference with ANAs through the L-ANCA system (Inmmunoconcepts®). Results were evaluated by the Generic assay kit ELISA® and CytoBead® ANCA (Generic Assays) to confirm positivity to MPO and/or PR3.The technical performance was evaluated by correlation analysis with Kappa values for data in which ANCAs was assessed at least by two techniques. Subsequently positivity of ANCAs was determined in a small sample of patients with clinical manifestations of autoimmune disease Results: Positive ANCAS were found in 10.21% (340/3330) of the data, 40% (136/340) were C-ANCA and 60% (204/340) P-ANCA. Only 67 requests included specific anti-MPO and anti-PR3 assays, and 62.7% of these (42/67) were positive for ANCAs. ANAs were requested in 538 data resulting positive in 68.21% (367), predominantly homogeneous pattern. 12, 64% of ANCAs positive data were also positive for ANAs, with P-ANCA in 83.72% of cases. The technique comparison included 44 samples positive for ANCAs evaluated by L-ANCA, CytoBead ANCA and ELISA. The correlation analysis showed high concordance between CytoBead and ELISA for PR3 (K=1.00 p<0.05) and MPO (K=0.94 p<0.05). However, in the evaluation between CytoBead ANCA and ANCA-L, a very low concordance (K=0.17 p<0.05) was observed Conclusions: The results suggest there is interference of ANAs in the positive P-ANCA results. IIF is an excellent technique for screening the presence of ANCAs while other methods such as anti-PR3 and anti- MPO by ELISA or microparticles assays are required for confirmation References: Jennette JC, Falk RJ. Pathogenesis of antineutrophil cytoplasmic autoantibody-mediated disease. Nat. Rev. Rheumatol. 10, 463–473 (2014). Csernok E, Moosig F. Current and emerging techniques for ANCA detection in vasculitis. Nat. Rev. Rheumatol. 2014;10(8):494–501. Radice A, Bianchi L, Sinico RA. Anti-neutrophil cytoplasmic autoantibodies: Methodological aspects and clinical significance in systemic vasculitis. Autoimmun Rev 2013;12:487–95. Disclosure of Interest: None declared